Fluorescence detection of fluorescein and SYBR green-stained DNA by reflective cavity-coupled fluorometer – A quantitative study. (15th October 2020) - Chen, Cheng-fu
Graphical abstract: Highlights: Customer-made, high-sensitivity fluorescence detector using reflective cavity for detection enhancement. Combinatorial, comparative quantification of fluorescence on the same platform of reflective cavity-coupled fluorometer. The need for a protocol for the SYBR Green-DNA solutions with a consistent dye-base pair ratio. Abstract: With a miniaturized, reflective cavity-coupled fluorometer, a new fluorescence detection technique is presented with a quantitative analysis of its limits and sensitivity in detection. This paper is on a comparative study of fluorescence detection, on the same modularized fluorometer platform, to various combinations of light sources, optical filter lenses, reflectivity of the cavity wall, and fluorophore models. The quantitative comparison results allows for scrutinizing the mechanisms of noises in each measurement, including Raman scattering, and determining the limit of detection (LOD). This fluorometer enables detection of fluorescein at 0.4 nM and of SYBR Green (SG)-stained DNA at 0.05 ng μl −1 when equipped with a 450 nm laser diode, 550 nm cut-on longpass optical filter, and a polished reflective cavity. The detection of DNA can be further improved to a lower LOD by addressing the uncertainty in preparing the SG/DNA solutions with a consistent dye-base ratio throughout all the sample solutions.